Improving ADR reporting in Jordan: a qualitative exploration of pharmacists’ perspectives - Suleiman, Amal K. (Frontiers in Medicine, 2025)
BackgroundCommunity pharmacists are most accessible to patients. Hence, they have a crucial role in ensuring drug safety by detecting and reporting adverse drug reactions (ADRs). However, there may be gaps in their knowledge of ADR reporting systems and barriers they face in reporting.ObjectiveThis study aims to assess community pharmacists’ knowledge of ADR reporting systems in the Kingdom of Jordan, identify the barriers they face in reporting ADRs, and explore the broader factors that influence their involvement in pharmacovigilance activities.MethodsIn-depth, semi-structured, face-to-face interviews were held with 20 community pharmacists from different regions of Jordan to evaluate their understanding of ADR reporting, the obstacles they encountered, and the elements that could motivate them to report ADRs. The interviews were transcribed and subjected to thematic analysis to find recurrent themes and insights. The thematic analysis highlighted opportunities for continuing education and an absence of formal training as the main barriers to ADR reporting.ResultsPharmacists reported dissatisfaction with time limits in their hectic work situations and the complexity of reporting procedures, especially the length and information demanded by ADR reporting forms. Another factor influencing low reporting rates was a perceived lack of acknowledgment and feedback. Participants proposed that encouraging ADR reporting with professional recognition or compensation and improving and digitizing the reporting process would promote increased participation.ConclusionADR reporting presents considerable difficulties for community pharmacists in Jordan, mostly because of administrative obstacles and an absence of official support and training. Enhancing pharmacovigilance efforts in Jordan could be achieved by providing incentives, simplifying the reporting procedure, and incorporating reporting into the current pharmacy management software.